THE PROBLEM OF FORMATION VIEWS ON HEALTH IMAGE LIFE IN ADOLESCENCE - T. V. Mayacova (Вестник Мининского университета, 2017)
This paper investigates the influence of personality traits on the stress levels in their professional activities . We assume that the level of stress is correlated with certain personality traits , and is enhanced by the development of the personality traits that facilitate adaptation.